2020
DOI: 10.21462/jeltl.v5i3.424
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Problems and Solutions in Writing an Argumentative Essay on Gender Issue

Abstract: <p><em>This study is intended to find out the students’ problems and their solutions in writing argumentative essays.  The subjects of this study were the fourth-semester students of English Education study program, Faculty of Pedagogy and Psychology, University of PGRI Wiranegara in the academic year 2019-2020. This study used Byrne’s classification in 1995 about writing problems, namely psychological, linguistic, and cognitive. This uses descriptive quantitative design. The instruments were docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This means that more than half of the total respondents stated that in making an essay, they often have difficulty in finding ideas. This finding is in line with previous research by (Ozfidan & Mitchell, 2020;Setyowati et al, 2020) that the difficulties commonly experienced by students in writing argumentative texts are the organization of writing, thesis statements, scientific references, supporting evidence, opinions. disclaimer, academic tone, content, and writing development.…”
Section: Discussionsupporting
confidence: 92%
“…This means that more than half of the total respondents stated that in making an essay, they often have difficulty in finding ideas. This finding is in line with previous research by (Ozfidan & Mitchell, 2020;Setyowati et al, 2020) that the difficulties commonly experienced by students in writing argumentative texts are the organization of writing, thesis statements, scientific references, supporting evidence, opinions. disclaimer, academic tone, content, and writing development.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it can be concluded that mechanics was difficult for the students. This finding corresponds with previous studies (e.g., Beniche et al, 2021;Rahmatunisa, 2014;Setyowati et al, 2020). In particular, Beniche et al (2021) observed sixty-eight Chemistry and Engineering Science students in Morroco and found that they encountered errors in punctuation and capitalization.…”
Section: My Difficulty Is About the Punctuation And I Don't Know If I...supporting
confidence: 91%
“…In Thailand, Ka-kan-dee and Kaur (2014) observed 60 English major students who were trained writers and found out they experienced difficulties in vocabulary, grammar, providing solid evidence, organization, time constraints, organizing ideas, writing a thesis statement, and understanding the topic. In Indonesia, many university students face linguistic, cognitive, and psychological problems in argumentative writing (Rahmatunisa, 2014;Saputra, Jumariati, & Febriyanti, 2021;Setyowati, Agustina, Sukmawan, El-Sulukiyyah, & Mabaroh, 2020). In addition, Indonesian undergraduate students confronted difficulties with insufficient grammar and vocabulary, pitching arguments, writing habits, topic unfamiliarity, and critical thinking (Fajaryani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The teacher might use social media like Facebook to teach writing (Annamalai, 2017), or using Self Regulated Strategy (Sartika & Rachmanita, 2017), or implement Collaborative Writing on Google Docs (Valizadeh, 2022). One of the most important keys and successful ways to enhance the students writing is when the student has a difficulty in writing, the English teacher should find a solution to solve it (Setyowati et al, 2020).…”
Section: Discussionmentioning
confidence: 99%